2009
DOI: 10.1063/1.3115812
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for high saturation of porous amorphous carbon films by noble gases

Abstract: Results of the electron diffraction study of Kr and Xe deposits on amorphous porous carbon substrates are reported. We have observed mixtures of crystallites typical of condensates formed at such substrates at low deposition temperatures. However, in the warming process at temperatures about three-to-five degrees below the sublimation point characteristic of flat substrates, the diffraction patterns demonstrate that large crystallites gradually disappear and a highly disordered matter forms. Such transformed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…CHs already demonstrated high capturing ability with respect to different gases including CO 2 . 7,8,[11][12][13] In our preliminary research, 13 we have found that the CO 2 uptake in CHs is very strong and the complete desorption of carbon dioxide captured in the carbon honeycomb matrix does not occur, even at high enough temperatures. This means that CHs used as membranes are very promising materials for CO 2 capturing.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…CHs already demonstrated high capturing ability with respect to different gases including CO 2 . 7,8,[11][12][13] In our preliminary research, 13 we have found that the CO 2 uptake in CHs is very strong and the complete desorption of carbon dioxide captured in the carbon honeycomb matrix does not occur, even at high enough temperatures. This means that CHs used as membranes are very promising materials for CO 2 capturing.…”
Section: Introductionmentioning
confidence: 89%
“…In order to study any gas sorption in CHs, we developed and tested the specific procedure, enabled us to fill nearly fully all available positions inside CHs. 7,8,[10][11][12] In this method, we first make deposition of gases at low temperatures below the known gas sublimation points, and then heat gradually our condensates till the temperatures 2-3 degrees lower these points and keep deposited gases at these temperatures for several minutes monitoring the electron diffraction patterns. Typically, the well-defined peaks from polycrystalline gas deposits disappear, but distinct residual signals left showing that some kind of composites based on CHs with sorbed gases form.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…在 Nina V. Krainyukova 等人 [122] 的研究工作中, 制备出来的蜂窝碳因其表面具有大量的孔道结构而 显示出优异的吸附能力, 同时也证实了先前的相关报 道 [122] 。研究人员在 23 K、40 K 和 78 K 的环境下在 蜂窝碳基底上分别对 Kr、Xe 和 CO2 进行沉积 [123] Nina V. Krainyukova 在 2017 年提出了一种吸 收 Ar、Kr 和 Xe 原子的蜂窝碳排列结构,并且认 为是最合理的排列方式 [124]…”
Section: Co 2 和惰性气体的吸附unclassified
“…The recently synthesized carbon honeycomb structure [14] is an exceptionally stable carbon allotrope. Absorption of the heavier rare gases such as krypton and xenon in carbon films obtained by deposition of vacuum sublimated graphite was studied a few years earlier [15]. It was found in particular that the levels of gas absorption attain 4-6% in atomic count with respect to the number of carbon atoms in such substrates.…”
Section: Introductionmentioning
confidence: 99%